Modelling and simulation of an advanced charging system for electric vehicles - Abdul Hassan bin Jaafar (Kulliyyah of Engineering, International Islamic University Malaysia, 2016)
Internal combustion (IC) engine powered motor vehicle accounts for about 22.9 % of the total national greenhouse gas (GHG) emissions in Malaysia. Governments had recognized that the environmental threats facing by the World today could be minimized by reducing the impact of the IC engine powered motor vehicle. The need to reduce the emission is paramount, as Malaysia has pledged to reduce 40% of CO2 emission in year 2020 from 2005 level by reducing 25% of the average fuel consumption. The introduction of electric vehicles (EVs) is one of the initiatives. However, the electric vehicles have not been commonly used by people nowadays due to the charging infrastructure. The aim of this study is to model an advanced on-board charging system for the EVs/HEVs all over the nation with three charging modes: slow charging with charging current of 25 A, medium charging with 50 A and fast charging with 100 A. Based on the battery size that need to propel an electric vehicle, charging process with the three modes was simulated. Besides, the simulation and experiment of advanced charging system has been conducted on a scale down battery pack with nominal voltage of 3.75 V and capacity of 1020 mAh. Result shows that the battery could be charging less than 1 hour with fast charging mode. However, due to limitation of Tenaga Nasional Berhad (TNB) power grid, the maximum 50 A current is considered to be the optimized passive mode for the EV's battery charging system. The developed advanced charger prototype performance has been compared with the simulation result and conventional charger performance. The maximum variation has been found to be about 17%; this close agreement between the advanced charger prototype, simulation model and conventional charger validate the prototype model. Furthermore, based on the result presented in this report, the battery to be charged up to 85% of its rated capacity by constant current mode only, which could shorten the battery charging time by 16% and prolong the battery life by 10%.